BUSINESS RISK MANAGEMENT IN ISLAMIC INSTITUTIONS AND BANKS: A PERSPECTIVE - ADIL DARWISH AL ZAABI; ADIL DARWISH AL ZAABI; ALI AHMAD ALKAABI (International Journal of Innovations in Engineering Research and Technology, 2021)
The banking sector frequently confronts several challenges and risks concerning their operations. These risks can hamper everyday operations, cripple the business system, and cause financial loss. In this regard, this study strives to propose the objectives and measures of risk management in Islamic institutions and banks to consolidate the concepts of Islamic banking. The researchers highlighted the types of risks that Islamic banking tends to avoid and the efforts to deal with them. Furthermore, it also recommended measures to circumvent the challenges faced by Islamic financial institutions, i.e., lack of experts regarding risk management and the weak risk management system. Thus, the paper also suggested several recommendations, such as diversification of investment and financing tools to reduce risks, attract savings, and diversify resources.